Pathology of experimental amoebic gill disease in Atlantic salmon, (Salmo salar L.), and the effect of pre-maintenance of fish in sea water on the infection - Zilberg, D; Munday, BL (2000)
Atlantic salmon were exposed to amoebic gill disease (AGD) immediately following their acclimatization to sea water (group 1), or following a 2 week period of maintenance in sea water (group 2). Three fish from each group were sampled on days 0, 1, 2, 4, 7, 14 and 28 post-infection. Characteristic gill lesions began to occur between days 2 and 4, and dramatically increased by day 7. The number of gill lesions on fish from group 2 was significantly higher than on fish from group 1 on days 7 and 14 (P<0.001), but the two groups did not differ in any other parameter. Histologically, Paramoeba sp., the aetiological agent of AGD, could be seen on the gills of fish as soon as 1 day post-exposure, attached to healthy-appearing gills. Gill pathology in the form of hyperplasia and lamellar fusion followed shortly. AGD infection was accompanied by a significant increase in the number of gill mucous cells (P= 0.002). Different methods for the diagnosis of AGD are discussed.